Histological Study of the Digestive Tract of Liza abu (Heckel) 3- Intestine - Abid, Wijdan Basheer; Diaa, Hanan Raad (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The study includes histological structure of pyloric caeca , intestine and rectum of Liza abu , the results show that the pyloric caeca are non-branched fingerlings structures numbering (4) and length rate was (0.5) cm , while the intestine of Liza abu was long narrow tube composed of a number of laps , the anterior part of intestine was wider in diameter than the posterior part , the length of intestine was (32) cm , the rectum was straight tube extends from the end of posterior part of intestine to the anus. The wall of pyloric caeca , intestine and rectum consists of main layers : mucosa , submucosa , muscularis and serosa , lining epithelium of pyloric caeca , intestine and rectum were simple columnar consisting of enterocytes having goblet cells in between , goblet cells react positively with PAS and AB in intestine and rectum , and with PAS only in pyloric caeca , tunica submucosa was a thin layer of dense connective tissue , tunica muscularis consists of smooth muscle fibersarranged in two layers : internal circular and external longitudinal , tunica serosa was thin layer of loose connective tissue surrounded by mesothelium .